NON-CARCINOGENIC RISK ASSESSMENT OF GROUNDWATER IN SOUTHERN PART OF SALEM DISTRICT IN TAMILNADU, INDIA - P. Balamurugan; P.S. Kumar; K. Shankar; R. Nagavinothini; K. Vijayasurya (Journal of the Chilean Chemical Society, 2020)
The main objective of this study was to evaluate the groundwater quality for domestic, agriculture use and to describe fluoride contamination in groundwater and their impacts on human health. 67 groundwater samples were collected and analyzed for major ions. Water Quality Index (WQI), Piper diagram and Gibbs diagrams were calculated to measure the suitability of groundwater for drinking purpose. The hazards index value was calculated to estimate the noncarcinogenic risk to adult (male, female) and children suggested by the United States Environmental Protection Agency (USEPA). The irrigation indices were calculated to evaluate the quality of water for irrigation purpose. Statistical methods such as principal component and hierarchical cluster analysis were used to analyses the inter-relationship of data. Hydrochemistry of the samples shows, the major ions in the order of Ca2+>Mg2+>Na+ and Cl->SO4-  in the study area. WQI value of groundwater, 74.62% of sample locations are good and 25.38 % of sample locations need primary treatment for drinking purpose. The results of the hazards index show that 65.67% of the sample locations exceeds the tolerable limit for non-carcinogenic risk (greater than one) for children higher than the risk level for Male and female. Statistical report of PCA and HCA reveals that Ca-Na-HCO3-F has positive loading and TDS-EC has negative loading. The study results show that rock-water interaction and anthropogenic activities are the major factors that influence the quality of groundwater. The continuous intake of excess concentration fluoride causes bone diseases and teeth problems.